Science Teaching and Learning: Teachers and Children Plan Together - Zoe Donoahue (Networks: An Online Journal for Teacher Research, 2003)
When I started teaching, the science curriculum was not prescribed for each grade. We were able to teach topics that we knew were captivating for children of a certain age and to share our particular passions and knowledge with our students. Many a time a whole unit of study would evolve from a "teachable moment". A child bringing in a robin's egg or a rock collection would pique our interest and we would pursue that topic until we had satisfied our curiosity. We were covering the same skills that the curriculum now details, children were learning how to learn about science topics, but this learning was in the context of a topic that was initiated by them. These days, five science topics are assigned to each grade and they must be taught that year. As a teacher, I feel that I have lost that element of choice and that it is more difficult for children to feel empowered and involved in shared decision making about the content of the curriculum. Fortunately, the government does not (yet) tell teachers how they should go about teaching each topic, so this is an area about which there can be some negotiation and co-planning with the students.